2016
DOI: 10.1016/j.jchromb.2015.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Determination and characterization of total thiols in mouse serum samples using hydrophilic interaction liquid chromatography with fluorescence detection and mass spectrometry

Abstract: Biothiols such as homocysteine, cysteine, and glutathione play many biologically important roles, especially in reduction-oxidation homeostasis and resistance to oxidative stress, and the measurement of their concentrations in model animal fluids is important in clarifying the pathology of thiol-related diseases. In this study, an analytical method for total biothiols in mouse serum using hydrophilic interaction liquid chromatography (HILIC) with fluorescence detection was developed. Mouse serum samples were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…In our previous study, we found two unknown thiols in the plasma of 129SV mice, which were confirmed to possess an SBD-S moiety and molecular weights of 1184.519 (SBD-T1 -) and 800.281 (SBD-T2 -) by HILIC-electrospray negative ionization-mass spectrometry [14]. In this study, two peaks (peaks 7 (SBD-T1) and 8 (SBD-T2) in Fig.…”
Section: Separation Of Biological Thiols In Cbs Deficient Mice Plasmasupporting
confidence: 61%
See 2 more Smart Citations
“…In our previous study, we found two unknown thiols in the plasma of 129SV mice, which were confirmed to possess an SBD-S moiety and molecular weights of 1184.519 (SBD-T1 -) and 800.281 (SBD-T2 -) by HILIC-electrospray negative ionization-mass spectrometry [14]. In this study, two peaks (peaks 7 (SBD-T1) and 8 (SBD-T2) in Fig.…”
Section: Separation Of Biological Thiols In Cbs Deficient Mice Plasmasupporting
confidence: 61%
“…Plasma samples were stored at -80°C until use. Pretreatment of plasma samples was carried out according to a previous report [14]. Briefly, MPG was added to plasma samples, and disulfides in the samples were reduced to their thiol forms by TCEP for total biothiol (=disulfide+thiol) quantification.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common method for determination of thiols is high-performance liquid chromatography (HPLC) [5]. In our previous studies [6,7], we utilized hydrophilic interaction chromatography (HILIC) to separate thiols in biological fluids, including human plasma and mouse serum. Pretreatment was followed by reduction with tris(2-carboxyethyl) phosphine (TCEP), deproteinization, and derivatization with ammonium 7-fluoro-2,1,3-benzoxadiazole-4-sulfonate (SBD-F).…”
Section: Introductionmentioning
confidence: 99%
“…109,110 A variety of analytical methods have been developed for analysis including HPLC, GC, and CE coupled with UV and fluorescence detection. [106][107][108][111][112][113][114][115][116][117][118] These methods require pre-or post-column derivatization and involve a less sensitive, complicated, and time-consuming procedure.…”
Section: Cysteine Metabolismmentioning
confidence: 99%